Persepsi masyarakat terhadap Pengkid di Malaysia (Public perception of Pengkid in Malaysia) - Abdul Rahim, Adibah; Dzulkifli, Mariam Adawiah; Rokis, Rohaiza (Akademia baru, 2017)
‘Pengkid’ is a term used to refer to a woman with masculine appearances and is prone to same gender sexual orientation. It is different from the term lesbian who is female homosexual and who experiences romantic love or sexual attraction to other females. ‘Pengkid’ has been prohibited by the National Council of Fatwa (Majlis Fatwa Kebangsaan), but the problem is still seriously spreading in the society. By using both quantitative and qualitative methodologies, this paper aims at identifying the characteristics of ‘pengkid’. In addition, the paper aims to identify contributing factors that lead to the spread of ‘pengkid’, as well as studying the relationship between pengkid and their level of religious understanding. This paper also provides suggestions and plans of actions to curb the increasing problems of ‘pengkid’ in society. The study has highlighted several physical and behavioural indicators of pengkid. It also identified three main contributing factors for the problem of pengkid, namely, individual and parents/family, environment, and religion. Furthermore, the study has found that the level of religious understanding and its practices has a direct impact on the lifestyle of a pengkid.